Contribution Of Locus of Control to Students' Academic Procrastination: A Systematic Literature Review - Tyara, Rizka; Mulawarman, Mulawarman; Sunawan, Sunawan; Mulyani, Petra Krtisti (Grief and Trauma, 2023)
This systematic literature review aims to compile and describe the contribution of locus of control to students' academic procrastination. One approach to literature study is a Systematic Literature Review (SLR). This research uses a systematic literature review using the Prisma method. To maintain the accuracy of the assessment and prevent errors in information in data analysis, cross-library checks are carried out, and re-reading the literature and paying attention to the reviewer's comments. The results of this study show that the relationship between Locus of Control and academic procrastination is positive. This illustrates that the higher the Locus of Control, the lower the students' academic procrastination. Locus of control is an important factor in reducing academic procrastination because the greater the value of a person's locus of control, the more that the individual can control himself, which makes him able to be responsible for his obligation.